Fiber Bragg Grating Monitoring of Full-bolt Axial Force of the Bolt in the Deep Strong Mining Roadway - Peng Wang; Nong Zhang; Jiaguang Kan; Zhengzheng Xie; Qun Wei; Wenhao Yao (Sensors, 2020)
With the increase of mining depth and strength, the evolution of bolt axial force is increasingly becoming important for ensuring the reliability and safety of support. To improve the problem of the existing coal mine roadway pressure-monitoring method, whereby it is difficult to continuously monitor the axial force of the bolt over a long period of time, a full rod fiber bragg grating (FBG) force-measuring bolt and system were designed based on the principle of fiber grating sensing. It was found that a trapezoidal groove is a relatively better groove. The linearity between the center wavelength offset of the fiber grating and the axial force was more than 0.99, and the conversion formula between the axial force of the bolt rod and the wavelength change of the fiber grating were obtained. The real-time monitoring revealed that the axial force of the bolt obviously changed before and after compression. The axial force distribution curve can be divided into the stable zone, growth zone, and peak zone. The influence of the roadway abutment pressure was approximately 130 m ahead of the working face, and the peak area was within the 25–35 m range of the advance working face. The axial force of the bolt rod at the end of the anchorage linearly increased with the tail end of the bolt, the axial force of the free segment was the largest, and the overall stress was essentially the same. The application results demonstrate the feasibility and effectiveness of the FBG full-length force bolt.